2016
DOI: 10.11124/jbisrir-2016-2441
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and management of fatigue in everyday life among adult patients living with heart failure

Abstract: Further qualitative research is needed to consider cultural factors of importance for managing fatigue in everyday life among patients with heart failure. Furthermore research should explore and test different kinds of physical and mind-body activities on the patients' functional capacity and wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…However, no males were represented in the sample and the NYHA classification level was not adjudicated through provider or records review, thus it questions if the sample was representative of class III and IV patients, as the authors described. Recently, Schjoedt et al (2016) reported Hagglund et al's findings along with findings from four other studies in their systematic review of qualitative data on fatigue. The five studies had a combined sample of 61 with an appropriately spread for gender and age for the heart failure population.…”
Section: Introductionmentioning
confidence: 93%
“…However, no males were represented in the sample and the NYHA classification level was not adjudicated through provider or records review, thus it questions if the sample was representative of class III and IV patients, as the authors described. Recently, Schjoedt et al (2016) reported Hagglund et al's findings along with findings from four other studies in their systematic review of qualitative data on fatigue. The five studies had a combined sample of 61 with an appropriately spread for gender and age for the heart failure population.…”
Section: Introductionmentioning
confidence: 93%
“…Fatigue is associated with restricted physical ability [38] and along with dyspnea and increased NYHA classification is associated with diminished QoL [40]. Schjoedt et al [41] reported that the unpredictability and the fluctuation of fatigue are associated with several limitations in daily activities and increased dependency on others. Patients try to maintain balance between adjusting to and struggling against fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review found decreased physical capacity, unpredictability, and varying intensity which where central features of fatigue experiences, which cause limitations in performing daily and social activities, increased dependency of others and loss of self‐esteem, identity and intellectual function in patients with CHF. Patients’ management of fatigue and its consequences was a process involving activities to handle fatigue (Schjoedt, Sommer, & Bjerrum, ). It was shown in another study that managing disease behaviour and discomforts of illness symptoms patients with CHF may be helped to improve their functional status (Herr et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients' management of fatigue and its consequences was a process involving activities to handle fatigue (Schjoedt, Sommer, & Bjerrum, 2016). It was shown in another study that managing disease behaviour and discomforts of illness symptoms patients with CHF may be Why is this research needed?…”
Section: Introductionmentioning
confidence: 99%